Improving frequency and proficiency of breast self-examination: effectiveness of an education program. - Mamon, J A (1985)
A randomized trial to improve breast self-examination (BSE) performance among college-age women was developed and results evaluated at a large public university. The major intervention was a BSE group education session conducted in classroom and workshop settings. The pre-intervention and six-months-after experimental-control comparisons show that: current performance of BSE increased by 26 per cent, bi-monthly or more often BSE performance increased by 29 per cent, and performance proficiency improved by 22 per cent. A change index, adjusting for each group's level on these three measures at pre-intervention, showed higher levels of change; 57 per cent, 36 per cent, and 28 per cent, respectively. A significantly larger proportion of women in the experimental group discussed BSE with others than women in the control groups. The "talked to" mothers, compared to the "not talked to" mothers performed BSE more regularly, in more positions, and spent more time on the examination. The results from this study suggest that properly targeted educational programs can significantly improve early detection behaviors in women. In addition, the evaluation protocol defined proficiency measures and validated measurement tools. Subsequent studies need to examine the relation of proficiency measures to detection of abnormality and subsequent effect on morbidity and mortality, so that the debate about BSE efficacy can be scientifically addressed.